Supporters, followers, fans and flaneurs: a taxonomy of spectator identities in football - Richard Giulianotti (2002)
World football (or soccer) has undergone an intensive hypercommodification over the past decade or so. This article examines the impact of this process on forms of spectator identification with top professional football clubs. Drawing upon previous analyses by Taylor and Critcher (on football) and the theories of Bryan Turner (on body culture), the article advances four ideal types of spectator identity: supporters, followers, fans, and flâneurs. The broad trend in sports identification is away from the supporter model (with its hot, traditional identification with local clubs) and toward the more detached, cool, consumer-orientated identification of the flâneur.